Low velocity impact analysis of glass/kenaf hybrid composites for aerospace structural applications - Ismail, Muhammad Faizzuddin (2018)
The usage of natural fibres as a reinforcement in material composites has increased over time. This utilization had been applied widely in several regions of the world and has already reached maturity in terms of technology, infrastructure and cost competitiveness. Aerospace industries were looking forwards on fully utilized their structural components by using composites material towards environmentally friendly solutions. The application of hybrid composites can be utilized by reducing the usage of synthetic fibre and replacing them with natural fibre. Nonetheless, the applications of composites in aircraft’s structure is tends to develop, especially the use of hybrid composites for fuselage which has many conflicting requirements. Several issues are highlighted in this research such as the selection of natural fibre that suits the usage in aerospace structural applications and the most suitable weight percentage combinations of individual fibre in hybrid composites that approaching the original constituents. Hence, the objectives of this research can be summarised as follows: the mechanical properties of a hybrid composite of glass/ kenaf fibre were investigated, especially with regards to tensile strength and low velocity impact (LVIT) resistance. A non-destructive test (NDT) was conducted by using dye penetrant to inspect the damages after impact where those areas were measured and analysed. The compression after impact (CAI) test was also performed on the impacted hybrid composite samples to analyse further the damage progression of the sample from the compressive aspect. It was found that, through mechanical analysis, the hybrid composite with the combination of 75% weight percentage of glass fibre and 25% weight percentage of kenaf fibre had the best tensile properties that approaching the tensile strength of 100% glass fibre. Furthermore, the best selected sample may experience LVIT impact forces up to 40 Joule. The higher impact force had led to larger damage and dents areas. CAI tests were carried out resulting in the decreases of the compression force exerted to the impacted damaged of the 40 Joule’s sample.